Peningkatan omzet usaha umkm melalui tehnik pembukuan sederhana dalam Komunitas Maju Kuliner (KOMAKU) - Marlinah, Aan; Rahayuningsih, Deasy Ariyanti; Deborah, Deborah (UKInstitute, 2024)
The community service activities with the title “A simple bookkeeping” was held by Trisakti School of Management (TSM) cooperation with MSMEs associated with KOMAKU on July, 5, 2023 time 19.00 WIB until finish through zoom meeting. The purposes of the activity is to increase the knowledge of MSMEs actors in bookkeeping technic until they have a capability in setting the financial statement. The training activity was intended to MSMEs actors to understand the accounting role especially in financial transaction bookkeeping techniques in MSMEs. Komunitas Maju Kuliner (KOMAKU) which spread all over cities in Indonesia as a community under supervision of chef Desi, a master chef from cooking competition on television. Furthermore, the speaker of TSM explained the material about the accounting cycle and the simple bookkeeping process. The material can increase the curiosity participant in joining the question and answer session. At the end of program, participant has shown the sense of satisfaction in understanding the series of bookekeeping stages through explaination of speaker in order to be implemented in their MSMEs. Finally, MSMEs actors in KOMAKU are able to understand the financial aspect such as the process of simple bookkeeping even though there is such another important aspect as the center of attention such as financial planning and marketing strategy of product that can help the actors to make success of MSMEs activities.